Trajectories of Hybrid Governance: Legitimacy, Order and Leadership in India - Miriam Wenner (Development and Change, 2021)
This article analyses the relationships between legitimacy, leadership and stability of hybrid orders in spaces of contested state authority. Complementing studies on public authority, the analysis builds on the observation that hybrid orders are often violent and unstable. The article goes beyond the one-sided views of legitimacy that focus on the legitimating registers of non-state governing authorities and which ignore for the most part the perceptions and evaluations of such strategies by the governed. It does so by conceptualizing legitimacy as a relational property, which emerges between governing authorities and the governed. Drawing on a case study from Darjeeling in West Bengal, India (where hybrid order appears in the domains of development and security), this article finds that non-state leaders tend to withdraw from hybrid agreements in order to regain legitimacy and trust when confronted with threats to their regional dominance. The stability of hybrid orders is not only dependent on the abilities of competing authorities to adapt to changing and conflicting normative and factual demands of their constituents, but is also an outcome of the struggle over the normative and moral bases of such evaluations.
Keywords: 300